'A space for you to be who you are': an ethnographic portrait of reterritorializing Indigenous student identities. Issue 3 (4th May 2017) - Anthony-Stevens, Vanessa; Stevens, Philip
ABSTRACT: This article explores the discourse practices of an Indigenous, community-based charter school and its efforts to create space for Indigenous both/and identities across rural–urban divides. The ethnographic portrait of Urban Native Middle School (UNMS) analyzes the discourse of making 'a space for you', which brings together rural and urban youth to braid binary constructs such as Indigenous and western knowledge, into a discourse of Indigenous persistence constraining contexts of schooling. We use the concept of 'reterritorialization' to discuss the significance of UNMS's community effort to create a transformative space and place of educational opportunity with youth. The local efforts of this small community to reterritorialize schooling were ultimately weakened under the one-size-fits-all accountability metrics of No Child Left Behind policy. This ethnographic analysis 'talks back' to static definitions of identity, space and learning outcomes which fail to recognize the dynamic and diverse interests of Indigenous communities across rural – urban landscapes.